Peran Fintech dalam Meningkatkan Daya Saing Perbankan Syariah di Era Digital - Puput Indriyani; Iyan Maulana Utama (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
In the current digital era, not all human needs can be separated from technology. Technological developments in the field of finance known as financial technology (fintech) mean that all companies, especially banking, including Sharia banking, must take advantage of the role of fintech as a tool to increase competitiveness in the digital era. The development and use of Sharia banking technology is still a matter of concern, because it is feared that it will not be in line with Islamic economic views. This research aims to analyze the ability of Sharia banking institutions in Indonesia to maintain their existence in the digital era. Bank Syariah Indonesia has the potential to survive in the current era by utilizing existing technology through human resources and the presence of fintech.